On Polish Fantastic Literature for Young People and Its Therapeutic Potential - Borowski, Dominik (Respectus Philologicus, 2017)
The objective of this article is to provide an overview of the therapeutic potential of fantastic literature for young people on the example of the series of novels by Rafał Kosik. The paper consists of three parts. The first part presents the definition of fantastic literature with reference to the concepts introduced by Tzvetan Todorov, Roger Caillois, Eric Rabkin and dictionary entries. Then the therapeutic function of literature is discussed by citing psychological theses on the importance of narrative in human life, as well as Roman Ingarden’s theory of the aesthetic experience. This provides the basis for reflection on bibliotherapy and the use of fantastic literature within its framework. The third part of the article presents the concept of the series of novels about Felix, Net and Nika, referring to the opinions of critics and literary scholars. Subsequently the selected fragments of the novels are discussed, demonstrating their therapeutic potential.
Keywords: Fantastic Literature for Young People; Bibliotherapy; Rafał Kosik